The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13007-022-00975-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cushion box and closed let-down ladder usage on damage to corn during handling: physiological deterioration

Abstract: Background Corn seeds have a high susceptibility to mechanical damage due to their large size and mass. The main purpose of this study was to evaluate the effects of the cushion box and closed let-down ladder usage in minimizing the negative influence of the free fall on the storage potential of corn seeds. Corn seeds were evaluated for the extent of physiological damage by measuring the seed deterioration by the accelerated aging test (percentage loss in germination in the accelerated aging te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This finding suggests that chickpea seeds with lower moisture contents are more resilient to physiological damage (reduction in germination percentage) compared to those with higher moisture values, which aligns with previous studies (Khazaei et al, 2008;Shahbazi, 2021;Shahbazi et al, 2017). The higher moisture contents may have led to increased flexibility in the seed tissues, transferring impact energy to the embryo and further reducing the germination percentage, as reported by Khazaei et al (2008) for wheat, Shahbazi et al (2012) for pinto beans, and Gu et al (2019) and Shahbazi and Shahbazi (2022b) for corn seeds. Higher seed moisture content can reduce mechanical seed coat damage at harvest (Uebersax et al, 2022).…”
Section: Effects Of the Moisture Contentsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding suggests that chickpea seeds with lower moisture contents are more resilient to physiological damage (reduction in germination percentage) compared to those with higher moisture values, which aligns with previous studies (Khazaei et al, 2008;Shahbazi, 2021;Shahbazi et al, 2017). The higher moisture contents may have led to increased flexibility in the seed tissues, transferring impact energy to the embryo and further reducing the germination percentage, as reported by Khazaei et al (2008) for wheat, Shahbazi et al (2012) for pinto beans, and Gu et al (2019) and Shahbazi and Shahbazi (2022b) for corn seeds. Higher seed moisture content can reduce mechanical seed coat damage at harvest (Uebersax et al, 2022).…”
Section: Effects Of the Moisture Contentsupporting
confidence: 89%
“…Seed deterioration is a dynamic process, with damaged areas gradually expanding to affect living embryonic tissues, leading to a decline in seed quality. Physical and physiological damage to the cell membrane is the primary cause of seed aging and deterioration, accompanied by enzymatic, respiratory, and hormonal changes, reduced protein production, genetic damage, and the accumulation of toxic metabolites (Shahbazi & Shahbazi, 2022b).…”
Section: Effects Of Drop Heightmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the amount of damage will increase. This is due to the increasing seed velocity with drop height, which results in a larger impact force (Fiscus et al, 1971;Shahbazi and Shahbazi, 2022c). Foster and Holman (1973) reported that when the drop height was more than 15 m, the velocity of the seed stream could exceed the single kernel velocity because, when the seed stream was dropped as a whole, the drag forces on the individual seeds were not all the same.…”
Section: Resultsmentioning
confidence: 99%
“…In order to reduce the drop height and speed of falling of the seeds when they leave the conveyors or during the unloading or loading of seeds storage bins, stepping falling systems (ladders) should be used (Shah et al, 2001). Two kinds of such systems, known as the cushion box and closed let-down ladder (Gregg and Billups, 2016;Shahbazi and Shahbazi, 2022c) are commonly used. These types of equipment can be installed in the path of seed transfer pipes or in the center of seed storage bins in order to unload or load bins while preserving the desired seeds in a safe state, without damage (Gregg and Billups, 2016;Shahbazi and Shahbazi, 2022a).…”
Section: Introductionmentioning
confidence: 99%